2021
DOI: 10.1021/acs.nanolett.0c04465
|View full text |Cite
|
Sign up to set email alerts
|

Topography, Spike Dynamics, and Nanomechanics of Individual Native SARS-CoV-2 Virions

Abstract: SARS-CoV-2, the virus responsible for the current COVID-19 pandemic, displays a corona-shaped layer of spikes which play a fundamental role in the infection process. Recent structural data suggest that the spikes possess orientational freedom and the ribonucleoproteins segregate into basketlike structures. How these structural features regulate the dynamic and mechanical behavior of the native virion are yet unknown. By imaging and mechanically manipulating individual, native SARS-CoV-2 virions with atomic for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 28 publications
(58 reference statements)
6
67
0
Order By: Relevance
“…Their findings suggest that the spikes interspacing is ∼15 nm and they reported other densities spaced 5 to 8 nm apart, connecting the RNP (ribonucleoprotein complex: composed by the N protein and the genome) to the membrane region, but could not confidently affirm if these densities were related to M or N proteins. For the SARS-CoV-2, Kiss et al 22 and Lyonnais et al 23 reported a “bald” viral particle showing a smooth surface, without clear smaller structures. Opposingly, our data show that the viral particle membrane is crowded with smaller structures, suggesting the structural description of the proteins on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings suggest that the spikes interspacing is ∼15 nm and they reported other densities spaced 5 to 8 nm apart, connecting the RNP (ribonucleoprotein complex: composed by the N protein and the genome) to the membrane region, but could not confidently affirm if these densities were related to M or N proteins. For the SARS-CoV-2, Kiss et al 22 and Lyonnais et al 23 reported a “bald” viral particle showing a smooth surface, without clear smaller structures. Opposingly, our data show that the viral particle membrane is crowded with smaller structures, suggesting the structural description of the proteins on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…For the indentation analysis, the measurements were done on the QNM Ramp Mode in fluid following the same protocol described by Kiss et al 22 Briefly, we also performed the measurements on the liquid mode, but in our case, the fluid used was culture medium solution (MEM). We used a force setpoint of 1 nN and a tip velocity of 50 nm/s, which, to our best knowledge, is lower than any other AFM study performed on the SARS-CoV-2.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the use of fiber mats for face masks to protect from COVID-19 is of current great interest. The virus is 62 ± 8 nm in size based on atomic force microscopy [ 35 ] and often travels in biological aerosols from coughing or sneezing that are 0.5–3 microns in size and prefer hydrophilic surfaces [ 36 ]. Current N95 masks have high filtration efficiency but are thicker than surgical masks and rather uncomfortable for long-term use in daily life.…”
Section: Resultsmentioning
confidence: 99%
“…Such evasion by the virus may not be an issue when it is capped by a wide pore as long as there are no other cross-reactions. 6) An interesting property of the SARS-Cov-2 virus is that the spherical membrane appears to be quite robust and resists mechanical attempts to change its shape [42]. Thus it is unlikely to squeeze through the pore of an e-cell.…”
Section: Discussionmentioning
confidence: 99%